Drug-related problems and associated factors among patients with kidney dysfunction at a tertiary hospital in southwestern Uganda: a prospective observational study - Kyomya, Julius; Atwiine, Fredrick; Shegena, Efrata Ashuro; Muhindo, Rose; Yadesa, Tadele Mekuriya (BMC nephrology, 2023)
Background: Kidney dysfunction is a common, progressive condition that is increasingly becoming a global public health issue. Because the kidneys are the major route for drug excretion, impaired renal function can change the pharmacokinetics and pharmacodynamics of drugs that are renally excreted. Additionally, patients with kidney dysfunction often have co-morbidities and the associated use of multiple medications which increases the risk of drug-related problem (DRP) occurrence. This study aimed to determine the prevalence, types, and factors associated with DRPs in patients with kidney dysfunction. Method: We conducted a prospective observational study over 3 months among hospitalized patients diagnosed with acute kidney injury or chronic kidney disease who were hospitalized in the medical ward, and patients attending the renal outpatient clinic at Mbarara Regional Referral Hospital. A total of 183 participants were enrolled through the use of a consecutive sampling technique. DRPs were classified according to the PCNE classification version 9.1. Data analysis was carried out using SPSS version 25. Results: A total of 174 patients with kidney dysfunction were included in the study with a mean ± SD age of 50.34 ± 18.13 years. A total of 219 DRPs were incurred by 138 (79.3%) study participants. The most common DRPs were ‘Untreated symptoms or indication’ (35.6%) followed by ‘adverse event (possibly) occurring’ (28.3%), and ‘effect of drug treatment not optimal’ (23.3%). Antimicrobials were the most involved drugs in suboptimal drug treatment (31.3%) and unnecessary drug treatment (32.1%). The study showed that length of hospital stay ≥ 5 days (AOR = 6.39, 95% CI: 1.75–23.27; p-value = 0.005) significantly increased the risk of DRP occurrence. Conclusion: The current results, in agreement with previous literature, showed a high burden of DRPs among patients with kidney dysfunction. Antimicrobials were the most involved drugs in suboptimal as well as in unnecessary drug treatment. Longer hospital stay significantly increased the risk of DRPs. The high prevalence of DRPs in patients with kidney dysfunction and the potential impact on antimicrobial resistance underscores the importance of regular medication reviews and close monitoring of patients with renal dysfunction.
Keywords: Drug-related problem; Kidney dysfunction; Acute kidney injury; Chronic kidney disease; Medication management